The Effect of Carbohydrate Fractionof Hyacinth Bean (Lablab purpureus (L). sweet) on the Blood Serum Cholesterol and Malonaldehyde of Rats Fed with High Cholesterol Diet] - Arif Hartoyo; Dahrulsyah Dahrulsyah; Nurheni Sripalupi; Purwono Nugroho (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2008)
The objective of this study was to analyze the effect of carbohydrate fraction of hyacinth bean (Lablab purpureus (L.) sweet ) diet on lipid profile and peroxydation value of the blood serum and liver of rats. Fifteen male wistar strain rats were divided into three diet groups of live animals. The first group was positive control group with standard diet. The third group was given carbohydrate fraction of hyacinth bean and 1% pure cholesterol. The experiment was conducted for 75 days. The total cholesterol levels in positive, negative control, and that in the hyacinth treated group were 204.0, 74,8, and 99.8 mg/dl. The LDL levels in the control, negative control group, the hyacinth treated group were 153.0, 20.6 and 45.9 mg/dl. Triglyceride levels in the positive control, negative control, and the hyacinth treated group were 121.4, 137.7, and 114.8 mg/dl. The atherogenic index in the positive control, negative control, and the hyacinth treated group were 6.9, 1.9 and 2.5 point. The total cholesterol and LDL levels in positive control, negative control, and the hyacinth treated group underwent hypercholesterolemia effect. Malonaldehyde content of the blood serum in positive control, negative control, and the treated group were 0.54, 0.48, and 0.31 Ã‚Âµmol/ml. Malonaldehyde content of liver organ in positive control group, negative control group, and the hyacinth treated group were 66.9, 36.4 and 73.4 nmol/g. Malonaldehyde content of blood serum in hyacinth treated group was significantly lower than that in the positive and negative control group. These result showed that the hyacinth group decreased free radical in the blood serum. On the other hand, the malonaldehyde content of the liver in all treatment showed no significant differences. Keywords : Carbohydrate fraction, Hyacinth bean, Lipid profile, Peroxydation.